1991
DOI: 10.1302/0301-620x.73b2.2005151
|View full text |Cite
|
Sign up to set email alerts
|

Functional anatomy of the anterior cruciate ligament. Fibre bundle actions related to ligament replacements and injuries

Abstract: This work studied the fibre bundle anatomy of the anterior cruciate ligament. Three functional bundles--anteromedial, intermediate, and posterolateral--were identified in cadaver knees. Their contributions to resisting anterior subluxation in flexion and extension were found by repeated tests after sequential bundle transection. Changes of length in flexion and extension and in tibial rotation were measured. None of the fibres were isometric. The posterolateral bundle was stretched in extension and the anterom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
444
1
64

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 655 publications
(536 citation statements)
references
References 12 publications
27
444
1
64
Order By: Relevance
“…However, the anterior cruciate ligament does not function as a simple band of fibers with constant tension as the knee moves. Its two bundles exhibit different tension patterns and are susceptible to different forces 30 . When the knee is extended, the posterolateral bundle is tight and the anteromedial bundle is moderately lax.…”
Section: Kinematicsmentioning
confidence: 99%
“…However, the anterior cruciate ligament does not function as a simple band of fibers with constant tension as the knee moves. Its two bundles exhibit different tension patterns and are susceptible to different forces 30 . When the knee is extended, the posterolateral bundle is tight and the anteromedial bundle is moderately lax.…”
Section: Kinematicsmentioning
confidence: 99%
“…1) by flexing and extending the knee to display their different tightening/slackening behaviour. In particular, the PL bundle becomes tight in knee flexion angles between 0° and 30°, whilst the AM bundle remains tight throughout flexion when an anterior displacement force is applied [2,5,19], allowing clear differentiation to be made between the two bundles. This is similar to that reported by Sakane et al [18] who used strain gauges to differentiate between the two bundles whilst passively flexing the knee.…”
Section: Introductionmentioning
confidence: 99%
“…This behavior is consistent with ACL anatomy, especially the antero-medial band, 32 which tightens in flexion. 33 Reuben et al 34 showed instability in AP tibial translations after ACL resection, up to about 608 flexion. In vivo studies showed abnormalities in rotation and translations in various activities after ACL injury, 35 although hamstrings function could alleviate this in stair ascent.…”
Section: Discussionmentioning
confidence: 99%